Carrying all before her : celebrity pregnancy and the London stage, 1689-1800 - Phillips, Chelsea (Performing celebrity., 2022)
"The rise of celebrity stage actresses in the long eighteenth century created a class of women who worked in the public sphere while facing considerable scrutiny about their offstage lives. Such powerful celebrity women used the cultural and affective significance of their reproductive bodies to leverage audience support and interest to advance their careers, and eighteenth-century London patent theatres even capitalized on their pregnancies. Carrying All Before Her uses the reproductive histories of six celebrity women (Susanna Mountfort Verbruggen, Anne Oldfield, Susannah Cibber, George Anne Bellamy, Sarah Siddons, and Dorothy Jordan) to demonstrate that pregnancy affected celebrity identity, impacted audience reception and interpretation of performance, changed company repertory and altered company hierarchy, influenced the development and performance of new plays, and had substantial economic consequences for both women and the companies for which they worked. Deepening the fields of celebrity, theatre, and women's studies, as well as social and medical histories, Phillips reveals an untapped history whose relevance and impact persist today"--